2019
DOI: 10.24018/ejbmr.2019.4.5.100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of Perceived Ease of Use and Perceived Usefulness on Consumer Attitude and Their Impacts on Purchase Decision on PT Tokopedia In Jabodetabek

Abstract: This study aims to analyze the effect of perceived ease of use and perceived usefulness on consumer attitudes and the impact on purchase decision at PT Tokopedia in Jabodetabek. Population in this study is the entire PT Tokopedia consumers in Jabodetabek, and the sampling method using purposive sampling. The data in this study were collected through questionnaire using Likert scale from 119 respondents who had transaction at least once in the last three months at PT Tokopedia. Data is processed using Linear St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 2 publications
2
13
0
3
Order By: Relevance
“…In this study, the PU of m-banking found to be significantly influenced the attitude towards it. Th is finding is consistent with existing TAM studies and also previous studies [14], [51], [55]. This imp lies that if the awareness of users in using m-banking increases i.e.…”
Section: Advances In Economics Business and Management Research Volume 177supporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the PU of m-banking found to be significantly influenced the attitude towards it. Th is finding is consistent with existing TAM studies and also previous studies [14], [51], [55]. This imp lies that if the awareness of users in using m-banking increases i.e.…”
Section: Advances In Economics Business and Management Research Volume 177supporting
confidence: 92%
“…Th is happens regarding the characteristics of users which they only intend to adopt a system if they are convinced the system would be helpful [50]. Also, the result also consistent with the study by [51] which states that PEOU is insignificant to users' attitudes. The easiness of using m-banking did not make people change their attitude to m-banking easily and quickly.…”
Section: Advances In Economics Business and Management Research Volume 177supporting
confidence: 75%
“…In particular, studies have shown that perceived usefulness affects online shopping behavior. For instance, Gunawan, Ali, and Nugroho (2019) examined the effect of perceived usefulness on consumer attitudes in Indonesia. The results demonstrated that perceived usefulness has a significant positive effect on consumer attitudes but has a positive and insignificant effect on the purchase decision.…”
Section: Perceived Usefulness and Online Shopping Behaviormentioning
confidence: 99%
“…This is because the public already understands the benefits of fintech, whose process is more efficient and effective compared to other financial services (Rahma, 2018). Perceived usefulness and perceived ease of use affect individual attitudes towards technology use, but the results of the study found that perceived usefulness had no significant effect on purchasing decisions (F. Gunawan et al, 2019). Perceived usefulness has a positive and significant effect on online shopping decisions during the covid 19 pandemic, where respondents feel the many benefits of online shopping, are comfortable shopping without leaving the house (Iriani & Andjarwati, 2020).…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Perceived usefulness has a significant positive effect on attitudes towards the use of fintech (Chuang et al, 2016). However, the research results are contradictory, perceived usefulness has no significant effect on purchasing decisions(F. Gunawan et al, 2019). The presence of e-wallet in various industrial sectors is a breakthrough in financial technology innovation that allows people to transact, buy and sell goods and services more easily, fintech technology provides a more transparent appearance on electronic payment systems (Gora, 2020).…”
Section: Introductionmentioning
confidence: 99%